Factors Influencing Student’s Behavioural Intention Towards the Use of E-Learning During Covid-19 in Malaysia - Sam Shun Jie,; Mohd Farid Fernandez, Dahlia Fernandez (Research in Management of Technology and Business, 2021)
Nowadays, many of the university students facing problem in the e-learning during the Covid-19 pandemic. This study aims to investigate factors influencing student’s behavioural intention towards the use of e-learning during Covid-19 in Malaysia. Students of University Tun Hussein Onn Malaysia (UTHM) will be selected as respondents and data will be collected from them. This study uses a quantitative method that is using an online survey form approach (Google Form) and simple random sampling technique. The researcher hopes that the result of this study can be used as a guidance and reference, especially for the management of the education as well as the relevant parties responsible for the organizational support experienced. This study will contribute to the body of knowledge on the influence of behavioural intention toward students in university by applying the technology acceptance model (TAM).